Occupational Safety in the Age of Artificial Intelligence: Reformation of the Indonesian Work Safety Law (Journal of Indonesian Legal Studies, 2024)
Artificial intelligence (AI) is undergoing rapid development globally, including in countries such as Taiwan and Indonesia. Taiwan, renowned as a world leader in hardware and semiconductor technologies, holds a significant advantage in AI advancement. This is further bolstered by governmental support through regulatory frameworks, policies, and funding initiatives, enhancing Taiwan's prowess in AI development. In contrast, Indonesia has also embraced the tide of technological progress, with its President declaring the nation's commitment to entering the 4th industrial revolution. Integral to this transition is the adoption of AI, recognized as a pivotal component of the aforementioned revolution. The collective technological advancements across Indonesia, Taiwan, and other nations invariably impact society, particularly the workforce. The integration of these futuristic technologies, predominantly within corporate settings, inherently alters labor dynamics and working conditions. This study scrutinizes the trajectories of AI development in both Taiwan and Indonesia, probing the compatibility of existing occupational safety and health legislation with the AI era. The findings underscore the perpetual evolution of technology and emphasize the imperative for nations to remain adaptive to emerging innovations. Furthermore, the study advocates for continuous updates to legal frameworks to align with the dynamic landscape of technological advancement.